RESPONS TANAMAN BUNCIS TIPE TEGAK (Phaseolus vulgaris L.) TERHADAP PEMBERIAN PUPUK KOMPOS DAN TSP - T. Edy Sabli; Selvia Sutriana (UIR Press, 2019)
The research was carried out in the experimental farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru during 6 months from July to December 2017. The study used Completely Randomized Design (CRD) with 2 factors. First factor was goat manure, consisting of 5 levels: 0, 5, 10, 15, 20 tons/ha and the second factor was TSP fertilizer, consisting of 4 levels: 0, 100, 175, 250 kg/ha. The materials used were bean seeds of the Balitsa-2 variety, goat manure, TSP fertilizer, Urea, KCl, Furadan 3G, Curacon 500 EC, Fungicide (Antracol), and 1 kg clear plastic. Parameters observed were flowering age, harvest age, number of pods per plant, pod weight per plant, pod length, and number of the remaining fruit. The tools used are a hoe, machete, rake, hand sprayer, analytical scale, meter, stationery, and camera. The results of the observations were analyzed statistically, and the further test was significantly different at a significant level of 5%. The results showed that the interaction and main effect of goat manure and TSP had a significant effect on all observated parameters. The best treatment was goat manure with a dose of 5 – 20 tons/ha and TSP at a dose of 100 – 250 kg/ha.